Membaca Ulang Orientalisme: Akar Historis dan Respons Intelektual Muslim: Revisiting Orientalism: Historical Roots and Muslim Intellectual Responses - Hadi, Sofian; Irawan, Dedy; Harwansyah, Iwan (Journal of Islamic and Occidental Studies, 2025)
This paper explores the dynamics of Orientalism in relation to the study of the Eastern world, particularly Islam, and examines the responses that have emerged from Muslim intellectuals. The study is motivated by the efforts of several Western Orientalists who systematically analyzed and interpreted Islamic teachings—including the Qur’an, Hadith, and Islamic history—with a tendency to diminish their values and authenticity. Using a critical textual analysis approach, this research examines Orientalist literature and Muslim intellectual responses. The findings reveal that Orientalist works often contain ideological biases and seek to influence Eastern perceptions to adopt a Western secular worldview, which frequently contradicts Islamic values. Muslim scholars have responded with strong critiques, targeting the motives, methodologies, and conclusions of Orientalist studies. This paper argues that Orientalism is not merely an academic endeavor, but also part of a broader ideological and political project aimed at dominating discourse and shaping the narrative of the Eastern world. The study highlights the urgency of developing a critical awareness of Orientalist productions and the need to strengthen authentic and balanced Islamic narratives.